Mechanism of Business Contract Drafting in Supporting Economic Activities - Muhammad Sood (Faculty of Law, University of Mataram, 2020)
The development of business contracts in supporting economic activities, especially in the trade sector, is inseparable from developments in the field of law. Thus, economic actors should understand the contract design method. This article aims to analyze the regulations of business contracts both nationally and internationally, and analize the mechanism of business contract draftingin supporting economic activity. This article is sourced from the results of normative legal research; therefore the method of approach used is the legal approach and conceptual approach. The results of the study indicates that the legal sources which form the basis for regulating business contracts include national law as regulated in Article 1457-1540 of the Civil Code; contract documents; international agreements in the field of contract; court decisions regarding business contracts; and doctrines in the field of contract law. The business contract mechanism includes 3 stages, namely: 1) Pre contractual includes: negotiations on the delivery, delivery and payment of goods; risk of loss if there is a default and procedure for resolving contractual problems; make a Memorandum of Understanding as an initial guideline for the understanding of the parties; Feasibility study concerning the prospects of business contracts made by the parties; 2) Contractual or contractual arrangements include, writing the initial manuscript, revising the manuscript, exchanging draft contracts, revising and writing the final manuscript, and signing of the contract. 3) Contract contractual or contract completion where the parties are responsible for providing guarantees or guarantees that the agreed contract is executed and completed properly. Understanding the mechanism of contract design will facilitate business activities carried out by the parties.